RESPON ORMAS KEAGAMAAN KOTA KEDIRI TERHADAP IDEOLOGI MANTAN ANGGOTA HIZBUT TAHRIR INDONESIA - Huda, Moh. Qomarul; Sulaeman, Mubaidi (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2022)
In this study, the researcher seeks to see the extent of the potential for conflicts with ideological backgrounds carried out by former HTI members due to their efforts to hegemony political and religious actions in the City of Kediri. The form of research used in this research is field research. Field research is a type of research oriented to the collection of empirical data in the field. Testing the data in this study using transferability analysis. Testing this data is a modification of external validity in qualitative research. The research that has been carried out has shown that in the City of Kediri the infiltration of former HTI is not much different from the initial goal of establishing HTI, namely preaching Islam by propagating the establishment of a caliphate (pan-Islamism) internationally and the enforcement of sharia law for all mankind. The movements of former HTI members in Kediri City are indeed banned from their activities by the Government, but the fact is that their ideology is still alive in Kediri City. This received a different response from NU and Muhammadiyah in Kediri. NU City of Kediri is the most vocal organization in preventing the growth and development of HTI ideology to revive in the City of Kediri. Meanwhile, Muhammadiyah of Kediri City is more lenient in dealing with the ideology of the former HTI member. Although in essence Muhammadiyah itself agrees with the dangers of the HTI ideology.